The Effect of The Project Based Learning Model on Students' Science Process Skills. : A Meta-Analysis - Zulaekah Zulaekah; Novianty Djafri; Tomi Apra Santosa; abdul rahman; Via Yustitia (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the effect of the project-based learning model on students' science process skills.This type of research is a meta-analysis. The research data sources came from 10 national and international journals. The process of searching data sources through google scholar, ScienceDirect, Eric Journal and Plos ONE. The keywords for searching data sources are project-based learning model and science process skills. Inclusion criteria are 1) international and national journals published 2015-2023; 2) Experimental or quasi-experimental type of research; 3) National and international journals indexed by SINTA, DOAJ, and Scopus; 4) Research has complete data t test, F test and standard deviation. Data collection techniques are observation and documentation through the database. Data analysis is quantitative statistical analysis with the help of the JSAP application. The results of this study concluded that the average effect size value (ES = 0.986) This finding shows that there is a significant effect of project-based learning model on students' science process skills.